2012
DOI: 10.3109/13693786.2011.584328
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility of ocular fungal pathogens recovered from around the world against itraconazole, voriconazole, amphotericin B, and caspofungin

Abstract: Although fungal infections of the eye are rare, they create an intractable clinical problem in ophthalmology because of the limited number of intravitreal and systemic therapeutic options. In this investigation, the in vitro efficacies of itraconazole (ITR), voriconazole (VOR), amphotericin B (AMB), and caspofungin (CAS) against 29 globally-collected ocular fungal isolates were assessed, following the standards that are outlined in the Clinical and Laboratory Standards Institute (CLSI) M38-A2 document. AMB [Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 26 publications
0
19
0
1
Order By: Relevance
“…6-13,16-28 These studies used different methods to report MIC (MIC 50 , MIC 90 , and range) and demonstrated variable MICs. The natamycin and voriconazole MIC 50 and MIC 90 found in our study for Fusarium isolates were within the range of published values for F. solani and for all Fusarium species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…6-13,16-28 These studies used different methods to report MIC (MIC 50 , MIC 90 , and range) and demonstrated variable MICs. The natamycin and voriconazole MIC 50 and MIC 90 found in our study for Fusarium isolates were within the range of published values for F. solani and for all Fusarium species.…”
Section: Resultsmentioning
confidence: 99%
“…Susceptibility studies investigating natamycin are also limited, as natamycin is used primarily for treating fungal keratitis. 6-10 The ocular studies that are present often have small sample sizes 5,11-13 or focus on one particular genus or species. 8-10 Here, we report the in vitro activity of natamycin and voriconazole against filamentous fungal isolates collected as part of a large, randomized comparative trial on fungal keratitis treatment, 14 and investigate the association between organism and MIC.…”
Section: Introductionmentioning
confidence: 99%
“…Lyophilized fungal strains were obtained from the reference collection of the CBS-KNAW Fungal Biodiversity Centre in Utrecht, The Netherlands. The antifungal susceptibility profiles of several isolates against AMB and VRC were described recently by our group [14,15].…”
Section: Study Isolatesmentioning
confidence: 99%
“…The biofilm activity of QC ATCC C. albicans 92228 was classified as ? (%Tbloc,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].The antifungal drugs VRC (Sigma, St. Louis, MO, USA), AMB (Sigma, St. Louis, MO, USA), and NAT (Sigma, St. Louis, MO, USA) were prepared according to the CLSI M38-A2 method [22]. Dilutions of all antifungals were prepared in RPMI 1640 medium (Sigma-Aldrich, Steinheim, Germany) buffered to pH 7.0 with 0.165 M MOPS (morpholinepropanesulfonic acid; Sigma-Aldrich, Steinheim, Germany) to yield final twofold drug concentrations of 0.03-16 lg/mL.…”
mentioning
confidence: 99%
“…3 For over a decade literature supports that voriconazole (VOR) could be a promising tool for the treatment of fungal infections of the eye, especially against most resistant species. [4][5][6] Now, to advance and to fully establish its role in treating keratitis in general, optimized topical drug delivery systems are extremely necessary. Considering previously cited sociodemographics of fungal keratitis, the final cost of the formulation could have a significant impact on the success of the therapy; therefore, it is also important that formulation constituents and production methods are nonexpensive.…”
mentioning
confidence: 99%